Comparison of production and economic dependence within the growing of sunflower in the Slovak Republic - Dobák Dušan; Katarína Klimentová; Roman Récky (Polityki Europejskie, Finanse i Marketing)
Growing of oil crops has spread considerably in the last years. The most important oil crop grown in our conditions is oilseed rape. Sunflower is the second most important crop grown in the Slovak Republic. In this paper we evaluate the growing of sunflower from the production and economic point of view. Only the years 1996, 2004 – 2009 are dealt with in the paper. Obtained results show that economic advantage of growing of sunflower is affected mainly by the climatic conditions as well as by the intensification of production and support policy. The year 2007 was economically most advantageous of evaluated years. The highest loss within the growing of sunflower was recorded in 2009. Higher hectare yield of sunflower can be achieved by the intensification of production.